Thermal and mechanical properties of a nanocomposite of a photocurable epoxy-acrylate resin and multiwalled carbon nanotubes - dos Santos M.N.* (2011)
In this work, thermal and mechanical behaviors of nanocomposites of a photocurable epoxyacrylate resin and multiwalled carbon nanotubes (MWCNT) were investigated. A combination of sonication, and mechanical and magnetic stirring was used to disperse 0.25. wt% and 0.75. wt% of MWCNTs into the resin. Two photocuring cycles using 12 and 24. h UV-A radiation were studied. Nanoindentation was the chosen technique for characterizing the modulus of elasticity and hardness of samples. The curing degree and glass transition temperature of the epoxyacrylate matrix and the nanocomposites were determined by Differential Scanning Calorimetry (DSC). In addition, the Vickers microhardness and nanocomposite morphology were also investigated by Scanning Electronic Microscopy (SEM) and Transmission Electronic Microscopy (TEM). The results indicate an increase in the stiffness and hardness of the material, and a shift in the glass transition temperature. The increase in the elastic modulus is in concordance with the predictions made by two simple models: rule of mixture and Halpin-Tsai equation. A fair agreement between nanoindentation and microhardness measurements is also found. Finally, the importance of curing degree in some of the properties investigated in this study is also discussed. © 2011 Elsevier B.V.